The Remainder Theorem
The remainder theorem is a formula used to find the remainder when a polynomial is divided by a linear polynomial. In this step-by-step guide, you learn more about the remainder theorem.

When a certain number of things are divided into groups with an equal number of things in each group, the number of things left is known as the remainder. This is what “remains” after division.
Step by step guide to the remainder theorem
The remainder theorem is expressed as follows:
When a polynomial \(a(x)\) is divided by a linear polynomial \(b(x)\) whose zero is \(x = k\), the remainder is obtained by \(r = a (k)\). The remaining theorem enables us to compute the remainder of dividing any polynomial by a linear polynomial without performing the steps of the division algorithm.
Remainder theorem formula
The general formula of the remainder theorem is given as follows:
\(\color{blue}{p(x)=(x-c).q(x)+r(x)}\)
When \(p(x)\) is divided by \((x-a)\): remainder\(=p(a)\)
OR
When \(p(x)\) is divided by \((ax+b)\): remainder\(=p\left(-\frac{b}{a}\right)\)
Notes:
- When a polynomial \(a(x)\) is divided by a linear polynomial \(b(x\)) whose zero is \(x = k\), the remainder is given by \(r = a(k)\)
- The remainder theorem formula is: \(p(x)=(x-c).q(x)+r(x)\)
- The basic formula to check the division is: Dividend \(=\) (Divisor \(×\) Quotient) \(+\) Remainder
The Remainder Theorem – Example 1:
Find the remainder when \(p(x)=3x^5-x^4+x^3-4x^2+2\) is divided by \(q(x):x-1\).
Replace the zero of \(q(x)\) into the polynomial \(p(x)\) to find the remainder \(r\):
\(x-1=0 → x=1\)
\(p(1)=3(1)^5-(1)^4+(1)^3-4(1)^2+2\)
\(=3-1+1-4+2\)
\(=1\)
Therefore, the remainder is \(1\).
The Remainder Theorem – Example 2:
Find the remainder when \(p(x)=x^3-x^2+x-1\) is divided by \(q(x):x+1\).
Replace the zero of \(q(x)\) into the polynomial \(p(x)\) to find the remainder \(r\):
\(x+1=0 → x=-1\)
\(p(-1)=(-1)^3-(1)^2+(-1)-1\)
\(=-1-1-1-1\)
\(=-4\)
Therefore, the remainder is \(-4\).
Exercises for the Remainder Theorem
- Find the remainder after \(2x^2-5x-1\) is divided by \(x-5\).
- Use the remainder theorem to evaluate \(f(x)=2x^5+4x^4-3x^3+8x^2+7\) at \(x=2\).
- Find the remainder when \(4x^3-5x+1\) is divided by \(2x-1\).
- Use the remainder theorem to find the remainder \((x^6+4x^5+9x^3-4x^2+10) \div (x+1)\).

- \(\color{blue}{24}\)
- \(\color{blue}{143}\)
- \(\color{blue}{-1}\)
- \(\color{blue}{-6}\)
Related to This Article
More math articles
- How to Convert a Linear Equation in Standard Form to Slope-Intercept Form?
- The Best School Supplies for Learning Math
- Top 10 5th Grade PSSA Math Practice Questions
- GED Math FREE Sample Practice Questions
- How to Solve Composition of Functions? (+FREE Worksheet!)
- How to Analyze and Understand Rational Functions: A Comprehensive Guide
- 10 Most Common SIFT Math Questions
- 8th Grade K-PREP Math Worksheets: FREE & Printable
- Exploring Line and Rotational Symmetry
- Top 10 3rd Grade MEAP Math Practice Questions
What people say about "The Remainder Theorem - Effortless Math: We Help Students Learn to LOVE Mathematics"?
No one replied yet.